Voices of Confinement and Rebirth: The Yellow Wallpaper, Daddy and Lady Lazarus - Aashna Arora (Emerging Trends in Languages, 2024)
Female authors in contemporary literature play a crucial role in reshaping the portrayal of mental illness, offering nuanced narratives deeply rooted in women's experiences. They address the complex intersection of mental health and societal expectations, exploring themes such as gender roles, body image, and trauma with sensitivity. These authors highlight women's unique challenges in treatment systems and advocate for gender-sensitive approaches in mental healthcare. Through diverse and complex characters, female writers challenge stereotypes and offer a broad spectrum of mental health conditions with empathy and sincerity. They employ literary techniques such as stream-of-consciousness, internal monologues, and symbolism to provide intimate insights into their characters' inner worlds, effectively externalizing their struggles and dilemmas. Female authors also confront the stigma surrounding mental illness, challenging discriminatory attitudes and societal pressures that deter individuals from seeking help. Their narratives foster empathy and understanding, promoting a more inclusive dialogue on mental health and encouraging help-seeking behaviors. Additionally, many female authors incorporate social commentary into their works, shedding light on systemic inequities exacerbating mental health disparities and advocating for structural reforms. In summary, the contributions of female authors to the representation of mental health in contemporary novels are profound and wide-reaching, enriching our understanding of mental illness and advocating for a more empathetic and supportive societal framework.
Keywords: Feminist movements; mental illness; misconceptions; societal pressure; women suffrage